The architecture of computer hardware and systems software an information technology approach - Englander, Irv (John Wiley & Sons, 2014)
The Architecture of Computer Hardware and System Software provides the right amount of technical detail needed to succeed in the field. This accessible introduction provides the basic principles of computer system architecture and organization in the context of the current technological landscape.